Teacher recruitment strategies and job performance in public senior secondary schools of Nigeria - Olaifa, Adeseko Sunday; Issa, Hammed Okiki; Niji-Olawepo, Olaide Abidemi; Adeoye, Moses Adeleke; Olaifa, Ebunlomo Oreoluwa (Journal of Educational Management and Instruction (JEMIN), 2023)
Teachers’ recruitment strategies are indispensable instruments for the selection of qualified and competent teachers. This study examined teachers’ recruitment strategies and job performance in public senior secondary schools in Kwara State, Nigeria. The study adopted a descriptive survey of correlational type. Two research questions and one hypothesis were raised to guide the study. The population of the study consisted of four hundred and two respondents in the 196 public secondary schools in Kwara State. The research instruments used were titled Teachers’ Recruitment Strategies Questionnaire” (TRSQ) and Job Performance Questionnaire (JPQ) were used to collect data for the study. Mean, Standard deviation and Pearson Product-Moment Correlation Statistics were used to analyze the data. The findings of the study revealed that there was a significant relationship between teachers’ recruitment strategies and job performance in public senior secondary schools in Kwara State (p-value .000 < significant level .05). It was recommended among others that Kwara State government through Kwara Teaching Service Commission (TESCOM), must endeavour to keep a high level of recruitment strategies to ensure and maintain the professional and competent spirit of teachers and good moral standard of the educational system in Kwara State.